Biotic pollination in Phaseolus coccineus: Impact on yield components and seed characteristics - Cué Hernández, Karina Alejandra; Gil Muñoz, Abel; Aguirre-Jaimes, Armando; López, Pedro Antonio; Taboada Gaytán, Oswaldo Rey (Ecosistemas y Recursos Agropecuarios, 2025)
Biotic pollination enhances yields of crops such as Phaseolus coccineus (runner bean), an important food legume in Mexico. Although some studies have assessed the effect of excluding pollinators in this species, it remains unclear whether agronomic management or flower color have additional effects. Thus, the objective of this study was to determine the significance of biotic pollination and to assess the effect of contrasting management systems and flower colors on the yield components and seed characteristics in P. coccineus. We examined the combinations arising from two systems (technified and traditional) and two varieties with flowers of different color (white and red), and compared plants with and without access of pollinators. We measured fourteen variables, which were analyzed by the Mann-Whitney rank test, cluster analysis, and principal component analysis. In all the management-variety combinations, plants with access of pollinators developed 97 % more normal fruits and seeds, compared to plants without access. Attributes such as seed length and width were greater in plants without pollinator access in both agronomic systems and varieties. The interaction with pollinators, and not management system or flower color, was the main explicative factor. Biotic pollination had beneficial effects on yield components, underscoring its importance for runner bean and highlighting the need to implement agricultural practices that conserve this ecosystem service in a sustainable manner.
Keywords: Runner bean; agronomic management; pollinators; productivity